Penerimaan Diri Penyandang Disabilitas - Elvia Agustina; Tience Debora Valentina (Universitas Ciputra Surabaya, 2023)
Persons with disabilities are people with special characteristics that have an impact on limitations in activities, so special treatment is needed to optimize their potential. Persons with disabilities' self-acceptance is influenced by the limitations they face. The limitations experienced make persons with disabilities feel stressed, low in self-esteem, and lonely. The purpose of this research is to determine the dynamics of self-acceptance in people with disabilities, particularly those with post-natal physical disabilities. This study used a literature review method with a narrative review type. The results of this study explain that there are four phases that persons with disabilities go through in the process of accepting themselves: rejection, conflict, adjustment, and acceptance.